Le ricerche in tema di societates publicanorum - Trisciuoglio, Andrea (Tesserae iuris, 2024)
Drawing on a 1992 essay by Ferdinado Bona on societates publicanorum, the article aims to clarify and discuss some recent views of Roman law scholars on the historical development of such societates, the internal relations between members, and the relations between such societates and the constitutional subjects in the late republic (contracting magistrates, senate, popular assembly, college of pontiffs)